2019
DOI: 10.1002/jcp.28996
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation agents increase the potential AraC therapy of AML by reactivating cell death pathways without enhancing ROS generation

Abstract: Acute myeloid leukemia (AML) has a poor prognosis and requires new approaches for treatment. We have reported that a combination of vitamin D-based cell differentiation agents (doxercalciferol/carnosic acid [D2/CA]) added following the cytotoxic drug arabinocytosine (AraC) increases AML cell death (CD), a model for improved therapy of this disease. Because AraC-induced CD is known to involve reactive oxygen species (ROS) generation, here we investigated if the modulation of cellular REDOX status plays a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…On the contrary, high‐intensity light induces phototoxicity by generating excessive ROS (40) and depresses or activates ion channels, which in turn can change intracellular Ca 2+ concentration (3). Such events lead to oxidative stress, prominent unfolded protein response and endoplasmic reticulum stress (40), leading to DNA damage, excessive autophagy and cell oppression (40–44).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, high‐intensity light induces phototoxicity by generating excessive ROS (40) and depresses or activates ion channels, which in turn can change intracellular Ca 2+ concentration (3). Such events lead to oxidative stress, prominent unfolded protein response and endoplasmic reticulum stress (40), leading to DNA damage, excessive autophagy and cell oppression (40–44).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, similar to 1.25D3, both 1.25D2 and its analogs could strongly cooperate with CA in inducing cell differentiation and inhibition of G1-S cell cycle transition [17]. Most recently, it has been demonstrated that activators of Nrf2 other than polyphenols, including clinically approved drug dimethyl fumarate, can also markedly potentiate the antileukemic effects of VDDs on AML cells both in vitro and in vivo [21].…”
Section: Int J Biol Chem (Online)mentioning
confidence: 99%
“…Besides their differentiation-enhancing activity, VDD/CA combinations can also potentiate the cyto-toxic effects of chemotherapeutics. Thus, it has been found that the combination of the clinically approved vitamin D 2 analog doxercalciferol and CA (D2/CA) significantly increases the extend of AML cell death caused by a low concentration of arabinosylcytosine (AraC) [21,22]. Notably, although AraC-induced cytotoxicity was accompanied by the increased generation of intracellular reactive oxygen species (ROS), the enhancement of cell death by D2/CA was accompanied by a decrease in ROS levels and by activation of VDR-dependent signaling pathway leading to ASK1-mediated apoptosis.…”
Section: Int J Biol Chem (Online)mentioning
confidence: 99%
“…Sorafenib action on HCC cells is known to generate ROS [14,15], but it has not been determined if the enhancement of the therapeutic effect of Sf by CA [13] is associated with an increased ROS production. We therefore measured cytosolic ROS levels following incubation of Huh7 and HepG2 cells with Sf (1 µM), CA (10 µM), and their combination [13] for 24 h using the fluorescent indicator DCFH [16][17][18][19][20]. Cells treated with the prooxidant H 2 O 2 (0.5 mM) for 30 min were used as the positive control ( Figure 1A).…”
Section: Carnosic Acid Potentiates the Prooxidant Effect Of Sorafenibmentioning
confidence: 99%
“…The intracellular ROS levels were determined using the oxidation-sensitive fluorescent indicator DCFH-DA, as described previously [16,18], with modifications. Vehicle control and treated cells (5 × 10 5 ) were harvested by trypsinization, washed with Hanks' Balanced Salt solution (HBSS) containing 10 mM HEPES (pH = 7.4) and loaded with 5 μM DCFH-DA in HBSS/HEPES buffer Huh7 and HepG2 cells were treated with the indicated agents for 24 hours.…”
Section: Determination Of Intracellular Levels Of Reactive Oxygen Spementioning
confidence: 99%